О двухтактном электромагнитном вибростенде с полигармоническим управлением - Божко, А.Е. (Видавничий дім "Академперіодика" НАН України, 2008)
The possibility for the reproduction of polyharmonic vibrations on a two-stroke electromagnetic vibrobench is investigated.